1983
DOI: 10.2136/sssaj1983.03615995004700060003x
|View full text |Cite
|
Sign up to set email alerts
|

Statistical and Stochastic Analyses of Hydraulic Conductivity and Particle‐Size in a Fluvial Sand

Abstract: An untilled medium‐grained fluvial sand near Socorro, N. Mex., was sampled in horizontal and vertical transects to study the statistical and stochastic properties of particle‐size parameters and saturated hydraulic conductivity. Hydraulic conductivity is log‐normally distributed, whereas the 10% finer, median, and geometric mean particle sizes are normally distributed. The strongest correlation between hydraulic conductivity and particle‐size distribution parameters is that of the log of hydraulic conductivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
2
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(61 citation statements)
references
References 0 publications
1
57
2
1
Order By: Relevance
“…Farthing et al [22] presented results for di↵erent porous media scenarios by using di↵erent types of sands. It has been shown [11,29,48] that although the permeability values can exhibit large spatial variations, these variations are not entirely random but spatially correlated. Previously, such fields have been modelled using a log-normal distribution assumption [39].…”
Section: Letmentioning
confidence: 99%
“…Farthing et al [22] presented results for di↵erent porous media scenarios by using di↵erent types of sands. It has been shown [11,29,48] that although the permeability values can exhibit large spatial variations, these variations are not entirely random but spatially correlated. Previously, such fields have been modelled using a log-normal distribution assumption [39].…”
Section: Letmentioning
confidence: 99%
“…In line with field studies [e.g., Byers and Stephans, 1983;Sudicky, 1986, Russo et al, 1997, axisymmetric anisotropy is adopted for C pp (x), i.e., I pv = I p1 and I ph = I p2 = I p3 are the characteristic length scales of p( x ) in the vertical (longitudinal) direction, and in the horizontal plane, respectively. The values of s p 2 for the various soil parameters of (14) were adopted from the Bet Dagan trench [Russo and Bouton, 1992] and are summarized in Table 1; the correlation length scales of the various parameters of (14) were assumed as equal to those of logK s , adopted from Russo et al [1997], i.e., I ph = I h = 0.8 m and I pv = I v = 0.2 m. Mean values of the soil parameters of (14) representing coarse-textured sandy and fine-textured clayey soils were adopted from Mishra et al [1989] and are summarized in Table 1.…”
Section: Characterization Of the Flow And The Transport Parametersmentioning
confidence: 99%
“…However, recent analyses of hydraulic conductivity data (Bakr, 1976;Byers and Stephens, 1983;and Hoeksema and Kitanidis, 1985) showed that although the hydraulic conductivity values vary significantly in space, the variation is not entirely random, but correlated in space. Such a correlated nature implies that the parameter values are not statistically independent in space and they must be treated as a stochastic process, instead of a single random variable.…”
Section: Statistical Representation Of Heterogeneitymentioning
confidence: 99%